Antioxidant Potential of Phoenix dactylifera Linn Extract and its Effects on Calcium Channel Antagonist in the Treatment of Withdrawal Syndrome in Morphine Dependent Rats - Mohd Adzim Khalili, Rohin; Ibrahim, H.Sani; Ibrahim, Sulaiman; Iliyasu, Zubairu (2018)
Date fruit Phoenix dactylifera (Linn) is remarkably known for its nutritional and numerous health benefits that are linked to its wide variety of bioactive compounds. Calcium channels were reported to play an important role in the mechanism of morphine dependence and withdrawal syndrome. This study examined the antioxidant potential of date fruit extract on calcium channel antagonists in the treatment of withdrawal syndrome in morphine-dependent rats. A total of thirty six (N=36) Sprague-Dawley adult male rats (weight 200-220 g) were used in this study. Morphine dependence was induced by subcutaneous injection of an increasing dose of morphine (ascending from 10 to 60 mg/kg) twice daily over a period of 5 days. The withdrawal syndrome was precipitated by administration of naloxone (i.p) 2 hours after the last morphine injection. For chronic study, the extracts or nifedipine were administered 30 minutes prior to each morphine injection, whereas the extract or nifedipine was only administered one hour after last morphine injection in acute studies. The rats were observed for the presence of withdrawal signs (jumps, tremor, eye ptosis, teeth chattering, wet dog shaking, diarrhoea and urination). The treatments suppressed withdrawal syndrome in morphine dependent rats. A statistically significant difference was observed between chronic and acute administration of extracts and nifedipine (p<0.001). The suppression of naloxone precipitated morphine withdrawal by the extracts possibly occurred via calcium channel blockage and the reversal of neuronal adaptation by its phenolic compounds. Therefore, Phoenix dactylifera could serve as an appropriate treatment of opioid addiction.